2021
DOI: 10.34133/2021/9793071
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Circuit Realization of Fast Quantum Search

Abstract: Quantum search algorithm, which can search an unsorted database quadratically faster than any known classical algorithms, has become one of the most impressive showcases of quantum computation. It has been implemented using various quantum schemes. Here, we demonstrate both theoretically and experimentally that such a fast search algorithm can also be realized using classical electric circuits. The classical circuit networks to perform such a fast search have been designed. It has been shown that the evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Meanwhile, the presented model is general, and can be applicable to other physical systems like photonic [45,46], acoustic [47,48], polaritonic [49] and mechanical systems [50]. Considering the rapid developments of this discipline [51][52][53][54][55][56], we believe that our work will stimulate considerable attention in a broad range of scientific and engineering communities.…”
Section: Discussionmentioning
confidence: 89%
“…Meanwhile, the presented model is general, and can be applicable to other physical systems like photonic [45,46], acoustic [47,48], polaritonic [49] and mechanical systems [50]. Considering the rapid developments of this discipline [51][52][53][54][55][56], we believe that our work will stimulate considerable attention in a broad range of scientific and engineering communities.…”
Section: Discussionmentioning
confidence: 89%
“…[1][2][3][4][5][6][7] Quantum walk (QW) on graphs plays an important role in the field of quantum algorithms. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Fast hitting, [5,6] which refers to a particle starting from the entrance node on a graph and trying to hit the exit node quickly, is one of the properties of QWs on graphs that quantum algorithms can take advantage of to demonstrate remarkable quantum speedup. Theoretical researches have shown that the fast hitting problem on unbalanced tree, which needs exponential time in classical algorithm, can be implemented within polynomial time based on QW algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] It has been proved that a fast search algorithm can be simulated using classical circuit. [16] But it is still a conundrum whether the unbalanced tree can be constructed directly using classical electric circuits to prove the quantum fast hitting with exponential speedup. Since the classical circuit technology is relatively mature, if such a way can be simulated, it is expected to have important impact on quantum speedup in classically intractable complex problems.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we experimentally explore the QSSM by designing circuit networks. Recently, based on the similarity between circuit Laplacian and lattice Hamiltonian, simulating various physical phenomena with electric circuits has attracted lots of interest [21][22][23][24][25][26][27][28][29][30][31][32][33]. Compared with other classical platforms, circuit networks possess remarkable advantages of being versatile and reconfigurable.…”
Section: Introductionmentioning
confidence: 99%